Teacher Education Strategies in the Interdisciplinary Teaching of Science, Mathematics, and Technical/Vocational Curricula - B.N. Kumar (European Scientific Journal, ESJ, 2014)
Educational development at the present time, and the year 2006 is characterized by two main aims: to enhance the content of education by making it more relevant and to improve the teaching/learning process. In science, both these aims have given rise to a number of projects which have attempted to link together the concepts and principles into an interdisciplinary or unified whole. The curricular materials generally include materials (texts and kits) for the students and guides for the teachers, once these are worked out way in advance; often these are so closely tied to the project/curriculum that teacher not directly involved in the project concerned have been only marginally influenced. It has also been observed/noted that when the trial phase of the interdisciplinary project (during which intensive training of teachers takes place) is over, many of teachers found it difficult to sustain the rhythm of implementation for a variety of reasons, much lip-service has been paid to the fact that teachers are agents of change and that central to any development or innovation is the role that they must play in language about that change, but little has been done to develop a theoretical framework in support of this role. In this direct, Professional Development Laboratory, PDL, has been working feverishly to produce a Model. Much teaching in the past emphasized content, today, the shift away from teaching facts to teaching skills pose a challenge if not a threat to all who are engaged in this enterprise.